Geomorphological constraining of tsunami (?) run-up in the Alcantarilha coastal lowland (Central Algarve, Portugal) - Dinis, Jorge (2016)
The Alcantarilha lowland, partly barred by a well developed barrier, including foredunes covering Pleistocene-Holocene beachrock and aeolianite, develops across the Alcantarilha infilled estuary, the beach-dune extending further SE until the Salgados lagoon. A topographic and coring survey revealed a peculiar feature at the leeward toe of the dune ridge close to the inlet area: a sandy fan with location, shape and morphology suggesting emplacement by single or multiple overwash of the barrier tip rather than tidal forcing. Its storm or tsunami origin and age are under investigation, and the only time-constrain available at present is that it should post-date ca. 6600 cal BP, the most recent in situ aeolianite (Moura et al., 2007) dated so far. METHODS, DATA SET AND RESULTS The fan boundaries are distinctive in aerial photos and satellite images: it is roughly ellipsoidal, ~200 m wide and ~300 m elongated paralleling the shoreline, rising ~ 0.9-1.2 m above the surrounding floodplain surface. Detailed topography shows that its short axis aligns with SW-NE elongated (though irregular) depressions in the dune crest, which link the beach with the fan. This could have favoured funnelling of, or erosion by, water overtopping the barrier but, in either case, the fan should correspond to extreme and abrupt event(s) of coastal flooding. 18 trenches and cores were performed in the exposed area of the fan and nearby flood plain to obtain samples and data on its sedimentology, lithostratigraphy and geometry. The fan consists of well sorted and rounded sand (Fig. 2). It thins away and wedges out landwards of the apex (located near Alc29T) where it is partly covered by dune sand. Its lower boundary is undulating and marked by textural contrast between sand (fan) and underlying mud (alluvial/lagoonal); an accumulation of marine-sourced perforated pebbles showing limited lateral continuity may pinpoint this boundary near the foredune (core Alc 25, ca. 80 m westward of profile in Fig.1); mud-balls were also observed immediately above this surface in cores and trenches. As the washover was probably emplaced in a barred lagoonal/estuarine floodplain setting, the fan’s northern outer belt is enclosed by low-energy sediments (not shown in Fig. 2).